LOESS LIKE LOAMS AS A SOIL FORMATION FACTOR FOR LIGHT-GRAY FOREST SOILS IN THE CHEBOKSARY REGION OF THE CHUVASH REPUBLIC - Vasiliev, O.A.; Semenov, V.G.; Tuleubayev, Zh.; Vasiliev, A.O.; Sarsembayeva, A.; Yesembekova, Z.T; Ziyaeva, G. (Scientific Journal of Pedagogy and Economics, 2020)
Covering loess-like loams are widespread in the Chuvash Republic and serve as parent rocks. They are heterogeneous both in the course and in the depth of occurrence. A distinctive feature of loess like loams from other overlying quaternary deposits is a sharp predominance in the granulometric composition of coarse dust fractions ranging in size from 0.05 to 0.01 mm, the content of which is 40% or more. Their granulometric composition varies from light loamy to clayey. Loess like loams, due to the peculiarities of their granulometric composition, have relatively good water permeability and moisture capacity and are superior to original loamy and clay parent rocks of the Permian and Jurassic systems in terms of these parameters. The content of moving forms of phosphorus and potassium (according to Kirsanov) in loess like loams is from 15 to 75 mg/kg, of exchange potassium - from 20 to 105 mg/kg. The soils formed based on them have a well-defined profile, the genetic horizons of which are easily diagnosed in the soil section. Because soils formed on loess like loams have well-developed genetic horizons, clearly manifested features of soil formation peculiar to each soil type, they occupy a central subtype and are diagnosed as typical. However, soils formed on loess-like loams and clays have low erosion resistance and marked as erosion threatening on soil maps.